The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15134439
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Ethanol Sensor via Defective Multiwalled Carbon Nanotubes

Abstract: This paper focuses on the fabrication of defective-induced nanotubes via the catalytic chemical vapor deposition method and the investigation of their properties toward gas sensing. We have developed defective multi-walled carbon nanotubes with porous and crystalline structures. The catalyst layer used in CNTs’ growth here was based on 18 and 24 nm of Ni, and 5 nm of Cr deposited by the dc-sputtering technique. The CNTs’ defects were characterized by observing the low graphite peak (G-band) and higher defect p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…[2] The sensor is also competitive to other types of ethanol sensors as shown in the comparison Table 3. Sensors based on pristine CNTFETs show only a weak response to ethanol, [28][29][30][31] and therefore only CNT-based sensors are listed where their response was enhanced by decoration with other materials or defect formation. Also not listed are MOF ethanol sensors that are based on capacitive and optical readout, [32,33] since those sensors appeared to be slow compared to an electrical readout of FET-type devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The sensor is also competitive to other types of ethanol sensors as shown in the comparison Table 3. Sensors based on pristine CNTFETs show only a weak response to ethanol, [28][29][30][31] and therefore only CNT-based sensors are listed where their response was enhanced by decoration with other materials or defect formation. Also not listed are MOF ethanol sensors that are based on capacitive and optical readout, [32,33] since those sensors appeared to be slow compared to an electrical readout of FET-type devices.…”
Section: Resultsmentioning
confidence: 99%
“…However, we can nevertheless consider in more detail the dynamics of the device. The sensor responds to charge accumulation and hence to the charging of adsorption sites at the Al 2 O 3 /MOF interface, which in turn depends on the diffusion of ethanol molecules through the MoS 2 /ZnO 30 s@500 ppm 220°500 ppm [39] Fe 2 O 3 /SnO 2 9 s@100 ppm 320°2 ppm [40] ZnO/SnO 2 1 s@30 ppm 225°0.5 ppm [41] Pt-Pd/MWCNTs Not specified 25°3 ppm [42] ZnO/MWCNTs 4 s@300 ppm 260°1 ppm [43] SnO 2 /MWCNTs 150 s@not specified 350°not specified [44] Defective MWCNTs 92 s@50 ppm 30°5 ppm [30] Defective SWCNTs 60 s@500 ppm 22°Not specified [31] Carbon nanobuds 60 s@50 ppm 22°50 ppm [31] GrO/aniline 0.03 s@500 ppm 25°500 ppm [45] Gr/ZnO NWs Not specified 125°1 ppm [46] MOF/graphene 5 s@100 ppm 25°100 ppm [2] MOF/CNT 10 s@10 ppm 25°≪ 1 ppb this work MOF layer. At the Al 2 O 3 /MOF interface, the ethanol molecules are then catalytically split into H + and alkoxy − , which eventually leads to a charging of the adsorption sites as discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, C 2 H 5 OH sensors are considered as important for the detection of spoilage of stored food. Thus, an ultra-sensitive C 2 H 5 OH sensor was developed based on highly defected CNTs [107]. The CNTs were fabricated by the PECVD method, as shown in Figure 4a.…”
Section: Recent Advances In C 2 H 5 Oh Gas Sensorsmentioning
confidence: 99%
“…Shalaan et al showed that when in an ethanol sensor MWCNTs were used to detect 50 ppm of the target gas, upon the exposure of reducing molecules, electrons were injected at the effective sites of CNTs' surface, then the electrons were released back when the gas was switched off. This caused first an increase and then a decrease in the measured resistance, showing the p-type behavior of CNTs [43]. Forming ZnO/CNT composite structure can increase the response dramatically and lower the optimum operating temperature for certain gasses [44].…”
Section: Introductionmentioning
confidence: 97%